Wage Rates as a Barrier to Entry: The Pennington Case in Perspective - Williamson, Oliver E. (Quarterly Journal of Economics, 1968)
Introduction, 85. — I. The allegations, 87. — II. The model, 90. — III. Wage barrier parameters in the bituminous coal industry, 101. — IV. Industry structure, 108. — V. Conclusions, 113.